2003
DOI: 10.1007/s00439-002-0834-z
|View full text |Cite
|
Sign up to set email alerts
|

Common variations in noncoding regions of the human natriuretic peptide receptor A gene have quantitative effects

Abstract: Genetic susceptibility to common conditions, such as essential hypertension and cardiac hypertrophy, is probably determined by various combinations of small quantitative changes in the expression of many genes. NPR1, coding for natriuretic peptide receptor A (NPRA), is a potential candidate, because NPRA mediates natriuretic, diuretic, and vasorelaxing actions of the nariuretic peptides, and because genetically determined quantitative changes in the expression of this gene affect blood pressure and heart weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 39 publications
(36 reference statements)
1
39
1
Order By: Relevance
“…Our observation that the CT6-containing GC-A promoter drives less transcription in human AoSMCs than the CT10-containing promoter is in contrast to the findings of Knowles et al, who reported that, in mouse AoSMCs, the transcriptional activity of the human CT6-containing promoter was significantly greater than the activities of the CT10-and CT11-containing promoters (15). One possible explanation for this discrepancy is that they used a promoter fragment extending from −770 bp to the ATG start codon to assess transcriptional activity, whereas we used a fragment extending from position −1425 to −41 bp.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our observation that the CT6-containing GC-A promoter drives less transcription in human AoSMCs than the CT10-containing promoter is in contrast to the findings of Knowles et al, who reported that, in mouse AoSMCs, the transcriptional activity of the human CT6-containing promoter was significantly greater than the activities of the CT10-and CT11-containing promoters (15). One possible explanation for this discrepancy is that they used a promoter fragment extending from −770 bp to the ATG start codon to assess transcriptional activity, whereas we used a fragment extending from position −1425 to −41 bp.…”
Section: Discussioncontrasting
confidence: 99%
“…Earlier reports also showed that the (CT)n= 6 allele is linked to an A at position −77 in the GC-A promoter region and that the (CT)n= 10 and 11 alleles are linked to a G at that position (15). We confirmed this linkage and found that the (CT)n= 9 and 12 alleles also are linked to a G at position −77.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…108,109 For GC-A, the association between a functional deletion mutation in the promoter region of the human GC-A gene, decreased receptor expression, and EH as well as ventricular hypertrophy has been shown in the Japanese population 110 but not in European patients with EH. 111 Knowles et al 112 recently identified 10 additional polymorphic sites in the noncoding sequence of GC-A and, by transient expression analysis, demonstrated that they can alter GC-A expression as much as 2-fold. Last, a promoter variant of the NPR-C gene has been shown to be associated with lower ANP levels and higher blood pressure in obese hypertensives.…”
Section: Relevance Of Alterations In the Anp/gc-a System To Cardiovasmentioning
confidence: 99%